Respon Antibodi Antikapsid pada Mencit yang Divaksin Vaksin Limpa dan Vaksin Kultur Virus Penyakit Jembrana - Manik Widiyanti, Ni Luh Putu; Suata, Ketut; Mantik Astawa, Nyoman; -, Hartaningsih (Jurnal Veteriner; Vol 10 No 2 (2009))
Bali cattle are one of Indonesia national asset which need to be conserved as they have many advantages.They are however susceptible to many infections diseases such as jembrana disease. Currently, thedisease is prevented by vaccination using vaccine derived from jembrana disease virus (JDV)-infected balicattle. An alternative vaccine using JDV-infected lymphocyte culture is expected to increase the virusyield and is therefore likely to increase the antibody response in the vaccinated animals. A study thereforewas therefore conducted to compare the anti-capsid antibody response of Balb/c mice immunized withvaccine derived from the spleen of infected cattle (spleen vaccine) and those immunized with vaccinederived from infected lymphocyte culture (culture vaccine). As many as 16 female Balb/c mice weredivided into two groups, Each group was vaccinated 4 times weekly respectively with spleen and culturevaccines. The antibody response against the capsid protein of JDV was determined using enzyme-linkedimmunosorbent assay (ELISA) and the absorbance reading of mice sera from each group was compared. Tstudentand univariate analysis showed that the average absorbance reading sera of sera derived frommice vaccinated with spleen vaccine (0.15) was not significantly different from those vaccinated withculture vaccine (0.18). It appears that culture vaccine is able to induce anti-capsid antibody response ashigh as spleen vaccine.
Keywords: Anticapsid antibody, spleen vaccine, tissue culture vaccine, jembrana disease virus